Role of primary and secondary surfactant layers on the thermal conductivity of lauric acid coated magnetite nanofluids - Lenin, Ramanujam; Joy, Pattayil Alias (Journal of Physical Chemistry C, 2016)
Lauric (dodecanoic) acid coated magnetite nanoparticles with different amounts of primary and secondary surfactant layers on the surface of the nanoparticles have been synthesized. Two sets of the surfactant coated nanoparticles are prepared; one with a comparable amount of primary surfactant and the other with a comparable amount of secondary surfactant. Nanofluids are prepared by dispersing the surfactant coated nanoparticles in toluene. Stability of the nanofluids is found to decrease with increasing amount of secondary surfactant on the surface of the nanoparticles, due to the increased hydrophilic nature of the particles in the nonpolar solvent. Thermal conductivity and viscosity of the nanofluids are found to increase with increasing amount of the secondary surfactant layer on the surface of the nanoparticles. The enhanced thermal conductivity for fluids with particles having a larger amount of secondary surfactant is ascribed to the lower dispersibility of the particles in toluene due to the exposure of the acid group of the surfactant to the hydrophobic solvent, leading to aggregation of the particles. Only a small increase in the thermal conductivity is observed for fluids with a larger amount of primary surfactant on the surface of the nanoparticles due to the increased dispersibility owing to the large number of hydrophobic tail groups of the surfactant. A larger enhancement in the thermal conductivity is observed in the presence of a small magnetic field for the fluids containing particles with a lower amount of the secondary surfactant. The overall results suggest that the thermal conductivity of the nanofluids depend on the amount and nature of the primary and secondary surfactants on the dispersed particles which in turn determine the interaction between the base fluid and the surfactant and therefore the dispersibility and stability of the nanofluids.